Improvement of greenhouse by reducing gas emissions using replacement policy - Al Ali, Yousif; Hrairi, Meftah; Al Kattan, Ibrahim (Inderscience Publishers, 2012)
This study aims to build a vehicle replacement model for air quality improvement by reducing the emission of greenhouse gases. The model based on linear programming with the objective to reduce the total cost considering different depreciation methods. The decision variables are; the mileage of the vehicles, age of the vehicles, the annual operating and maintenance costs, and the estimated cost of emissions hazard. The application of the proposed model is based upon the fleet replacement model for mid-sized vehicles in the transportation department of Dubai municipality in the United Arab Emirates (UAE). Retaining the current fleet policy without implementing a new replacement model will continue to increase the rate of CO2 emissions. The proposed replacement model has been tested using three different depreciation approaches. The results show that the proposed replacement model has reduced the gas emissions and improved air quality. This application could be used as a benchmark for many other transportation departments in the UAE. The model shows promising results for improvement of the fleet performance including the reduction of greenhouse emission.